SEROLOGICAL SURVEY FOR SELECTED PATHOGENS IN FREE-RANGING COUGARS (PUMA CONCOLOR) IN SÃO PAULO, BRAZIL - Franco, Paolla Nicole [UNESP]; Felippi, Daniel Angelo [UNESP]; Zanini, Dayane da Silva [UNESP]; Cunha, Caroline Muniz [UNESP]; Castilho, Pablo Menegon; de Barros, Luiz Daniel; Garcia, João Luis; Cavalcanti, Sandra Maria Cintra; Silva, Jean Carlos Ramos; Teixeira, Carlos Roberto [UNESP] (American Association of Zoo Veterinarians, 2023)
This study performed a serological assay to assess the exposure of free-ranging cougars (Puma concolor) to four selected infectious agents, including Toxoplasma gondii, Leptospira spp., the feline immunodeficiency virus (FIV), and the feline leukemia virus (FeLV). Serum samples were collected from 27 free-ranging cougars along the Tietê River Basin, in the central region of the State of São Paulo, Brazil. The presence of antibodies against T. gondii was detected in 59.3% (16/27) of the serum samples through the modified agglutination test (MAT-t), which was the most prevalent agent. The microscopic agglutination technique (MAT-1) was used to investigate the occurrence of anti-Leptospira spp. antibodies, showing that 11.1% (3/27) of the sampled cougars were seropositive. The only serovar detected was Djasiman (L. interrogans). A commercial enzyme-linked immunosorbent assay (ELISA) licensed for use in domestic felines was used to investigate the occurrence of retroviruses. The ELISA test kits detected a prevalence of 11.1% (3/27) of FIV antibodies, while none of the samples tested showed any evidence of FeLV antigen. These results suggest that free-ranging cougars are exposed to potentially pathogenic agents. This study presented the first recorded occurrence of the serovar Djasiman in P. concolor.